Enhanced absorption in ultrathin Si by NiSi2 nanoparticles. Issue 1 (January 2013) - Sachan, R.; Gonzalez, C.; Dyck, O.; Wu, Y.; Garcia, H.; Pennycook, S. J.; Rack, P. D.; Duscher, G.; Kalyanaraman, R.
Abstract : Various forms of Si including amorphous Si (a-Si) are important photovoltaic (PV) materials. However, in order to improve the cost-to-performance aspects of Si solar cells, such as by enabling ultrathin (<500 nm) Si solar technology, new strategies are required to improve optical absorption within Si, which is a relatively poor absorber of light in the visible solar spectrum. In this study, the authors demonstrate a potential approach to enhance optical absorption in ultrathin a-Si films by embedding nickel di-silicide (NiSi2) nanoparticles (NPs). The Ni silicide NPs were engineered inside 50 nm thick a-Si by thermal annealing of co-deposited Ni and Si thin films on Si and quartz substrates. A quantitative electron energy-loss spectroscopy analysis was used to accurately determine the composition of silicide NPs. From broadband absorption optical studies, integrated optical absorption was found to increase by ~85% in the visible solar range (350–750 nm) and by ~150% in the infrared range (750–3000 nm) for the NiSi2 NP incorporated amorphous Si films. Optical modeling captured the absorption behavior of NP embedded a-Si thin films, thus suggesting an efficient route to design new photo-absorber NPs for future Si based PV devices.